Percutaneous coronary intervention improves quality of life of patients with chronic total occlusion and low estimated glomerular filtration rate - Zhao, Shuai; Chen, Yan; Zhu, Boda; Wang, Jiayi; Wei, Zhihong; Zou, Yiming; Hu, Wentao; Chen, Genrui; Wang, Huan; Xia, Chenhai; Yu, Tiantong; Han, Peng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background A low estimated glomerular filtration rate (eGFR <90 mL/min/1.73 m2) is widely recognized as a risk factor for major adverse cardiac events (MACE) after percutaneous coronary intervention (PCI) for chronic total occlusion (CTO). However, the impact of successful CTO-PCI on quality of life (QOL) of patients with low eGFR remains unknown. Objectives The aim of this prospective study was to assess the QOL of CTO patients with low eGFR after successful PCI. Methods Consecutive patients undergoing elective CTO-PCI were prospectively enrolled and subdivided into four groups: eGFR ≥90 mL/min/1.73 m2 (n = 410), 90 > eGFR ≥ 60 mL/min/1.73 m2 (n = 482), 60 > eGFR ≥ 30 mL/min/1.73 m2 (n = 161), and eGFR <30 mL/min/1.73 m2 (n = 23). The primary outcomes included QOL, as assessed with the European Quality of Life-5 Dimensions (EQ-5D) questionnaire, and symptoms, as assessed with the Rose Dyspnea Scale (RDS) and Seattle Angina Questionnaire (SAQ), at 1 month and 1 year after successful PCI. Results With the decline of eGFR, CTO patients were more likely to present with comorbidities of hypertension, diabetes, hyperuricemia, and previous stroke, in addition to lower hemoglobin levels and left ventricular ejection fraction (p < 0.05). Low eGFR was associated with greater incidences of in-hospital pericardiocentesis, major bleeding, acute renal failure, and subcutaneous hematoma, but not in-hospital MACE (p < 0.05). Symptoms of dyspnea and angina were alleviated in all CTO patients with eGFR ≥30 mL/min/1.73 m2 at 1 month and 1 year after successful CTO-PCI, but only at 1 month for those with eGFR <30 mL/min/1.73 m2 (p < 0.01). Importantly, QOL was markedly improved at 1 month and 1 year after successful PCI (p < 0.01), notably at a similar degree between patients with low eGFR and those with normal eGFR (p > 0.05). Conclusion Successful PCI effectively improved symptoms and QOL of CTO patients with low eGFR.